PENGUNAAN ICE BREAKING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMAN 2 BAYANG KELAS XI DAN XII - Vira Hapena Putri; M. Isnando Tamrin (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Ice Breaking is one of the fun learning media by absorbing innovative, creative, futuristic elements. This study aims to determine the Use of Ice Breaking in Increasing Student Learning Motivation in Class XI and XII Islamic Religious Education Subjects at SMAN 2 Bayang. The research design was pre-experimental, namely the One Group Pre-Test and Post-Test Design. The subjects in this study were 56 students with data collection techniques using random quotas. The data analysis used in this study was the product moment correlation test. The statistical technique used was the Pearson Correlation Product Moment. The location of this research was at SMAN 2 Bayang Middle School. The data collection tool used was the Ice Breaking questionnaire. The motivation to learn PAI increased in students after the application of Ice. Breaking is 55.2% and the rest is influenced by other variables. Thus the research hypothesis is accepted, namely Ice Breaking has a significant and significant effect on students' motivation to learn PAI.